Milk phospholipids in correction of liver lipid profile in rats with tetracycline-induced fatty hepatosis - Gryshchenko, Viktoriia; Грищенко, Вікторія; Pototskyi, Andrii; Потоцький, Андрій; Veselskyi, Stanislav; Весельський, Станіслав; Danchenko, Olena; Данченко, Олена Олександрівна; Illek, Josef; Іллек, Йозеф (My University, 2025)
EN: The research relevance is determined by the limited information on the molecular mechanisms of fatty hepatosis development in mammals and the identification of effective markers for the diagnosis of this pathology. Timely diagnosis of fatty hepatosis is also relevant for the prevention of dangerous complications, primarily cirrhosis of the liver and hepatocellular carcinoma. Disorders in lipid metabolism are substantial in the pathogenesis of fatty hepatosis. Therefore, the study aimed to establish regular changes in the liver lipid profile in rats with artificially induced fatty hepatosis and the use of milk phospholipids as corrective therapy. For this purpose, thin-layer chromatography was used. The study determined that in the case of artificial reproduction of tetracycline hepatosis in the liver of rats, a deficient level of total lipid fractions is formed. The esterified cholesterol fraction undergoes particularly sharp changes, the content of which decreased by 51.3% compared to the control. Oral administration of a milk phospholipid based dietary supplement to sick rats prevented disruption of the lipid composition of the liver, which may indicate sufficient efficiency of absorption of the dietary supplement’s phospholipids in the intestine and a stimulating effect of its components on their endogenous formation in hepatocytes. In addition, deficient levels of liver phospholipid spectrum indicators were observed in sick animals. A decrease in the total fraction of inositol phosphatide and phosphatidylinositol by 26.6%, phosphatidylserine by 19.9%, sphingomyelin by 18.2%, phosphatidylcholine by 18.3% and phosphatidylethanolamine by 19.6%, and the restoration of their parameters when milk phospholipids were administered to rats. When the dietary supplement was administered to clinically healthy rats, a significant increase in the liver content of all fractions of total lipids and individual phospholipids was observed. Based on the results obtained, it is reasonable to recommend the bioactive supplement “FLP-MD” as a corrective therapy for lipid metabolism disorders in cases of functional liver disorders in animals with fatty hepatosis. /// UA: Актуальність наукового дослідження полягає в обмеженій інформації з питань молекулярних механізмів розвитку жирового гепатозу в ссавців та визначення ефективних маркерних показників у діагностиці цієї патології. Своєчасне діагностування жирового гепатозу також важливе для запобігання виникнення його небезпечних ускладнень, передусім, цирозу печінки та гепатоцелюлярної карциноми. Важливу роль у патогенезі виникнення жирового гепатозу відіграють розлади у метаболізмі ліпідів. Тому мета цього дослідження полягала у встановленні закономірних змін у ліпідограмі печінки щурів за штучного відтворення жирового гепатозу й застосування фосфоліпідів молока в якості коригувальної терапії. Для цього використовували метод тонкошарової хроматографії. Визначено, що у разі штучного відтворення тетрациклінового гепатозу в печінці щурів формується дефіцитний рівень загальних фракцій ліпідів. Особливо різких змін зазнає фракція естерифікованого холестеролу, вміст якого зменшився на 51,3 % порівняно з контролем. Пероральне введення хворим щурам біодобавки на основі фосфоліпідів молока запобігало порушенню ліпідного складу печінки, що може свідчити про достатню Ukrainian ефективність засвоєння фосфоліпідів біодобавки в кишечнику та стимулюючий вплив її компонентів на ендогенне їх утворення в гепатоцитах. Крім того, у хворих тварин відмічали формування дефіцитного рівня показників фосфоліпідного спектра печінки. Зокрема, зменшення вмісту сумарної фракції інозитолфосфатиду і фосфатидилінозитолу на 26,6 %, фосфатидилсерину на 19,9 %, сфінгомієліну на 18,2 %, фосфатидилхоліну на 18,3 % та фосфатидилетаноламіну на 19,6 % та відновлення їх параметрів за введення щурам фосфоліпідів молока. У разі застосування біодобавки клінічно здоровим щурам виявляли достовірне зростання в печінці вмісту всіх фракцій загальних ліпідів та індивідуальних фосфоліпідів. У відповідності до отриманих результатів обґрунтовано рекомендувати біоактивну добавку «FLP-MD» в якості засобу коригувальної терапії за розладів метаболізму ліпідів у разі функціональних порушень печінки за жирового гепатозу тварин.
Фосфоліпіди молока у коригуванні ліпідограми печінки у щурів за тетрациклініндукованого жирового гепатозу
Keywords: tetracycline hydrochloride; corrective therapy; thin-layer chromatography; lipid and phospholipid spectra; fatty dystrophy; тетрацикліну гідрохлорид; коригувальна терапія; тонкошарова хроматографія; ліпідний і фосфоліпідний спектри; жирова дистрофія